2010
DOI: 10.3346/jkms.2010.25.7.1077
|View full text |Cite
|
Sign up to set email alerts
|

Virilizing Adrenocortical Oncocytoma in a Child: A Case Report

Abstract: Functioning adrenocortical oncocytomas are extremely rare and most reported patients are 40-60 yr of age. To our knowledge, only 2 cases of functioning adrenocortical oncocytomas have been reported in childhood. We report a case of functioning adrenocortical oncocytoma in a 14-yr-old female child presenting with virilization. She presented with deepening of the voice and excessive hair growth, and elevation of plasma testosterone and dehydroepiandrosterone sulfate. She had an adrenalectomy. The completely rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 7 publications
(6 reference statements)
1
34
0
1
Order By: Relevance
“…An adrenocortical oncocytic neoplasm occurring with an aldosteronoma has been described [57,58] as well as very rare cases of virilizing adrenocortical oncocytic neoplasm in a female child [59][60][61] or old woman [62] , an adrenocortical oncocytic carcinoma producing testosterone [63] or presenting with pseudoprecocious puberty induced by adrenocortical oncocytoma [64] and an adrenal oncocytic neoplasm producing cortisol and testosterone [65] or cortisol and aldosterone [66] . A case of an adrenocortical oncocytic neoplasm producing interleukin (IL)-6 has been reported [67] .…”
Section: Diagnosismentioning
confidence: 99%
“…An adrenocortical oncocytic neoplasm occurring with an aldosteronoma has been described [57,58] as well as very rare cases of virilizing adrenocortical oncocytic neoplasm in a female child [59][60][61] or old woman [62] , an adrenocortical oncocytic carcinoma producing testosterone [63] or presenting with pseudoprecocious puberty induced by adrenocortical oncocytoma [64] and an adrenal oncocytic neoplasm producing cortisol and testosterone [65] or cortisol and aldosterone [66] . A case of an adrenocortical oncocytic neoplasm producing interleukin (IL)-6 has been reported [67] .…”
Section: Diagnosismentioning
confidence: 99%
“…However, Lim et al reported the case of a 14-year-old girl with a functioning adrenocortical oncocytoma who presented with virilization and high testosterone and dehydroepiandrostenedione sulfate (DHEA-S) levels. These authors classified this lesion as borderline [4].…”
Section: Discussionmentioning
confidence: 96%
“…Virilization is more often associated with malignant tumors [Latronico et al, 2001] rather than with secreting adenoma. Rare cases of mild clitoromegaly have been reported in adolescent girls with androgen-secreting adrenocortical oncocytoma [Lim et al, 2010]. More often, clitoromegaly is associated with cancers derived from secreting tumors of the ovaries of which 20% are granulosa cell tumors.…”
Section: Other Causes Of Virilizationmentioning
confidence: 99%
“…Malignant tumors, albeit extremely rare in girls, should be included in the differential diagnosis, because tumors like carcinoma, endodermal sinus tumor, sarcoma, and rhabdomyosarcoma may be a cause of clitoral hypertrophy [Gomes et al, 2013]. Finally, a mediastinal nonHodgkin's lymphoma involving the clitoris has been described in a 2-year-old girl as the first sign of the disease with no other symptoms [Lim et al, 2010].…”
Section: Other Tumorsmentioning
confidence: 99%